Tempo barroco: as Visitas Pastorais dos Comissários das Ordens Terceiras no século XVIII em Minas Gerais - DOI: 10.5752/P.2175-5841.2011v9n22p534 - Evangelista, Adriana Sampaio (Horizonte, 2011)
This article aims to examine the apparatus that marked the entrance of the Third Orders’ Commissioners on their visits to the villages, also analyzing how these pastoral visits took place. The Visitations of those Commissioners of the Third Order of Our Lady of Mount Carmel and San Francisco happened to be special occasions for the brothers of these congregations to be both materially and spiritually revived. In the material aspect, such visits demanded great costs to cover the ceremonies and the Commissioners expenses. The main purpose of the Visitation was to ensure the maintenance of a sense of order and hierarchy that originally was on the foundation of the fraternity. Thus, the Visitors should inspect and guide the administrative life of these congregations and also to help the Fathers to conform their lives to the precepts of morality and Christian faith and to the rules of the Third Order. Such visits also had the purpose to educate and to discipline those brothers who had committed some delict, and to curb practices and deviant behaviors. The pomp of the Baroque ceremonies that took place during the time of those mentioned visits finally aimed to raise the sense of order and hierarchy among all the members of Third Order of Our Lady of Mount Carmel and San Francisco.